Pengaruh Game Online terhadap Kemampuan Emosional Anak Usia 5-6 Tahun di Kelurahan Leok 1 Kecamatan Biau Kabupaten Buol - Grahitta Ainun Rizky; Mohamad Zubaidi; Setiyo Utoyo (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2022)
The purpose of the study was to investigate the effect of online games on the emotional abilities of children aged 5-6 years in Leok 1 Village, Biau District, Buol Regency. This study is an Ex-post facto quantitative study and the number of samples is 30 children. From the results of the study, there was an effect of I on children's emotional abilities by looking at the average value of x and y. This can be seen in X obtaining an average value of 31.06 while in Y data obtaining an average value of 49.06. Based on the output of the Statistical Test, it is known that sig.n(2-tailed) is 0.000. Because the value is 0.000 0.05, the hypothesis is accepted. Thus, the research hypothesis states that there is an influence of online games on the emotional abilities of children aged 5-6 years in Leok 1 Village, Biau District, Buol Regency. The influence that arises makes children easily rebellious, cry and sulk when the use of online games is limited.